1990
DOI: 10.1083/jcb.111.6.2939
|View full text |Cite
|
Sign up to set email alerts
|

cDNA cloning reveals the molecular structure of a sperm surface protein, PH-20, involved in sperm-egg adhesion and the wide distribution of its gene among mammals.

Abstract: Abstract. Sperm binding to the egg zona pellucida in mammals is a cell-cell adhesion process that is generally species specific. The guinea pig sperm protein PH-20 has a required function in sperm adhesion to the zona pellucida of guinea pig eggs. PH-20 is located on both the sperm plasma membrane and acrosomal membrane. We report here the isolation and sequence of a full-length eDNA for PH-20 (available from EMBL/GenBank/DDBJ under accession number X56332). The derived amino acid sequence shows a mature prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
0

Year Published

1993
1993
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 137 publications
(94 citation statements)
references
References 87 publications
3
91
0
Order By: Relevance
“…This protein is present on the posterior head and the acrosomal membrane of mammalian sperm. Via cDNA cloning, the amino acid sequence of the guinea pig protein could be elucidated (Lathrop et al, 1990). PH-20 is originally synthesized as a polypeptide with an apparent molecular weight of 64 kDa, and it is bound to the membrane via a glycosyl-phosphatidyl-inositol (GPI) anchor.…”
Section: Testicular Hyasementioning
confidence: 99%
See 1 more Smart Citation
“…This protein is present on the posterior head and the acrosomal membrane of mammalian sperm. Via cDNA cloning, the amino acid sequence of the guinea pig protein could be elucidated (Lathrop et al, 1990). PH-20 is originally synthesized as a polypeptide with an apparent molecular weight of 64 kDa, and it is bound to the membrane via a glycosyl-phosphatidyl-inositol (GPI) anchor.…”
Section: Testicular Hyasementioning
confidence: 99%
“…A comparison of the sequence of bee and hornet venom hyases Lu et al, 1995) with those of human, monkey, mouse, and guinea pig PH-20 protein (Lathrop et al, 1990;Y. Lin et al, 1993Y.…”
Section: Comparative Aspectsmentioning
confidence: 99%
“…It is expressed in both the testis and epididymis and is present in sperm and in the luminal fluid of the epididymis (Deng et al 1999, Zhang & Martin-DeLeon 2003a. The PH20 protein is widely conserved among mammals, and homologues have been cloned from many species including guinea pig, where the protein was first identified (Lathrop et al 1990), rat (Hou et al 1996), rabbit , fox (ten Have et al 1998), pig (Day et al 2002), monkey and man (Lin et al 1993).…”
Section: Introductionmentioning
confidence: 99%
“…The deduced amino acid sequence ofbee venom hyaluronidase shows no discernible similarity to the hyaluronidase from bacteriophage H4489A of S. pyogenes (2). A search in the EMBL data bank (13) revealed that bee venom hyaluronidase is related to PH-20, a protein located on the plasma membrane and the acrosomal membrane ofguinea pig sperm (6). The two polypeptides share 36% identity in a region encompassing amino acids 14-303 of the bee enzyme and 17-307 of PH-20 (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…As described in this paper, by using this information we were able to isolate two clones that encode the hyaluronidase precursor from a cDNA library prepared from bee venom glands. The sequence ofthis insect enzyme* shows homology to a protein present in guinea pig sperm (6).…”
mentioning
confidence: 99%